Behavioral Nudges to Improve Audit and Feedback Report Opening Among Antibiotic Prescribers: A Randomized Controlled Trial. (2nd March 2022) - Daneman, Nick; Lee, Samantha; Bai, Heming; Bell, Chaim M; Bronskill, Susan E; Campitelli, Michael A; Dobell, Gail; Fu, Longdi; Garber, Gary; Ivers, Noah; Kumar, Matthew; Lam, Jonathan M C; et al.
Abstract: Background: Peer comparison audit and feedback has demonstrated effectiveness in improving antibiotic prescribing practices, but only a minority of prescribers view their reports. We rigorously tested 3 behavioral nudging techniques delivered by email to improve report opening. Methods: We conducted a pragmatic randomized controlled trial among Ontario long-term care prescribers enrolled in an ongoing peer comparison audit and feedback program which includes data on their antibiotic prescribing patterns. Physicians were randomized to 1 of 8 possible sequences of intervention/control allocation to 3 different behavioral email nudges: a social peer comparison nudge (January 2020), a maintenance of professional certification incentive nudge (October 2020), and a prior participation nudge (January 2021). The primary outcome was feedback report opening; the primary analysis pooled the effects of all 3 nudging interventions. Results: The trial included 421 physicians caring for >28 000 residents at 450 facilities. In the pooled analysis, physicians opened only 29.6% of intervention and 23.9% of control reports (odds ratio [OR], 1.51 [95% confidence interval CI, 1.10–2.07], P = .011); this difference remained significant after accounting for physician characteristics and clustering (adjusted OR [aOR], 1.74 [95% CI, 1.24–2.45], P = .0014). Of individual nudging techniques, the prior participation nudge was associated with a significant increase in report opening (OR, 1.62 [95% CI, 1.06–2.47], P = .026; aOR, 2.16 [95% CI, 1.33–3.50], P = .0018). In the pooled analysis, nudges were also associated with accessing more report pages (aOR, 1.28 [95% CI, 1.14–1.43], P < .001). Conclusions: Enhanced nudging strategies modestly improved report opening, but more work is needed to optimize physician engagement with audit and feedback. Clinical Trials Registration: NCT04187742. Abstract : In this randomized controlled trial of 421 physicians caring for >28 000 long-term care residents at 450 facilities, the use of enhanced email nudging strategies was associated with modest improvements in opening of antibiotic audit and feedback reports.